Pengaruh Suplementasi Fe, Zinc dan Vitamin A terhadap Status Gizi Anak SD Stunted di Imogiri, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Tri Siswati, Hamam Hadi (Berita Kedokteran Masyarakat (BKM), 2003)
Background : The prevalence of stunting in Indonesian elementary school children is still high. It has been reported that micronutrient deficiency was associated with growth retardation. However, the effect of micronutrient supplementation on growth remains unclear.Objective : The-study was conducted to examine the effect of iron supplementation in combination with Zn and Vitamin A on growth nutritional status of stunted elementary school children.Method : The study was a randomized double blind placebo-controlled trial conducted in Bantul Regency in 2002. Stunted children aged 11-12 years were randomly assigned into four treatment groups : Iron group (n=38), Zinc + Iron group (n=41), iron + Vitamin A group (n=39), and Iron + Zinc + Vitamin A group (n=39). This study was done in August 2002-September 2003. Weight and height of each child were measured every month. Hb levels, Zinc plasma and Serum Retinol were measured at the start and the end of the study. Nutrient intakes of each child were collected by using multiple 24 hour recall.Result : The improvement in height for age Z-Score (HAZ) of children who received iron and vitamin A supplementation was higher than that of children who received Fe only (p=0.026). There was no significant difference in the improvement of height for age Z-score between children who received zinc + iron, or zinc + viaminvitamin A + iron and those who received Fe only (p>0.05). The effect of vitamin A and iron supplementation on HAZ the height for age z-score was modified by hemoglobin level;. T the effect of iron and vitamin A supplementation on the improvement of HAZ appeared mainly in children with initial hemoglobin level < 12.0 g/ There was no significant difference in the improvement of weight for age z-score and weight for height z-score between treatment groups.Conclusion :Iron and Vitamin A supplementation significantly improved Height for Age Z-Score (HAZ) of stunted elementary school children. Keywords: Supplementation, stunted, nutritional status, school children.